2016
DOI: 10.1111/bcpt.12664
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Changes among Users of Non‐Vitamin K Antagonist Oral Anticoagulants in Atrial Fibrillation

Abstract: Patients with atrial fibrillation discontinuing anticoagulant therapy are left unprotected against ischaemic stroke. Further, switching between oral anticoagulants may be associated with a transiently increased risk of bleeding or thromboembolism. However, there is a paucity of real-life data on pattern of switching and discontinuation of oral anticoagulants. To address this, we conducted a nationwide drug utilization study including all registered Danish atrial fibrillation patients initiating a non-VKA oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
71
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 37 publications
(54 reference statements)
13
71
2
Order By: Relevance
“…Several national/regional studies have reported increases in the number of DOAC users, despite the NVAF population used differing from ours . The incidence increased in both the males and females across the study period in most databases.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Several national/regional studies have reported increases in the number of DOAC users, despite the NVAF population used differing from ours . The incidence increased in both the males and females across the study period in most databases.…”
Section: Discussioncontrasting
confidence: 51%
“…To our knowledge this is the first cross‐national drug utilization study providing the incidence of DOAC use in NVAF patients at a national/regional level, across several European countries. Only a few, single country European studies with similar inclusion criteria have been published, which only provide number of DOAC users rather than incidence figures …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these DOAC users without a registered indication were older, more frequently had a history of ischaemic stroke, and more often received low‐dose DOAC compared with DOAC users with a registered indication. Therefore, the exclusion of DOAC users without a registered indication may constitute an important selection bias in observational studies based on the Danish health care registries, as pointed out previously …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sex distribution in our sample is similar to that of sex‐stratified data on all drug sales of OACs in Denmark in 2015 (made available from Danish online drug statistics ). In our study, no patients stated to fill NOAC due to ‘upcoming/recent knee‐ or hip replacement’, although register‐based studies have found this to be the indication of around 10% of all newly initiated NOAC treatments . This may be explained by these patients only being prescribed a NOAC once and therefore being less likely to be captured in this setting.…”
Section: Discussionmentioning
confidence: 60%